Need Analysis of Interactive E-Worksheet as a Source of Digital Learning based on Local Wisdom in Learning Folklore Texts - Tressyalina Tressyalina; Ena Noveria; Ermawati Arief; Ella Wulandari; Novia Tri Ramadani (AL-ISHLAH: Jurnal Pendidikan, 2023)
Worksheet refers to a document or a digital file that contains exercises, questions, or tasks for students to complete as part of their learning activities. This study aims to analyze the need for an appropriate interactive E-Worksheets in learning folklore texts. This research is a qualitative descriptive research. In this qualitative research, the research instrument is the researcher himself. The subjects in this study were students of senior high school in Padang. Data collection techniques in this study used a questionnaire. This data collection technique is in the form of a questionnaire filled out by students. Based on the results and discussion, it can be concluded that E-Worksheets   can increase students' interest in learning, especially in learning folklore texts. The implications of this research highlight the importance of incorporating interactive E-Worksheets in teaching folklore texts. Educators and curriculum developers can utilize these findings to design and implement digital learning materials that effectively engage students and promote a deeper understanding of cultural heritage.